Experiential Learning and the Power of Women - Falk, Thomas; Bartels, Lara; Steimanis, I.; Vollan, Björn (2022)
Thomas Falk*, L. Bartels, I. Steimanis, V. Duche, B. Vollan *Environment and Production Technology Division, IFPRI Virtual | November 3, 2022